2010
DOI: 10.1097/ypg.0b013e3283351153
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inheritance in recurrent early-onset depression

Abstract: Major depressive disorder (MDD) is believed to have a genetic factor in its pathogenesis. On the basis of studies in MDD showing brain energy depletion and maternal inheritance in some families, we hypothesize that some of the genetic factor is likely maternally inherited on the mitochondrial DNA (mtDNA). Six hundred and seventy-two pedigrees from the Genetics of Recurrent Early-Onset Depression project were analyzed for matrilineal/nonmatrilineal pairs. Pairs were constructed to control for sex, age and autos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The Genetics of Recurrent Early-Onset Depression (GenRED) project found that matrilineal relatives, i.e. those with the same mitochondrial genome as the proband, were more likely to suffer from a mood disorder than non-matrilineal relatives (Bergemann and Boles, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The Genetics of Recurrent Early-Onset Depression (GenRED) project found that matrilineal relatives, i.e. those with the same mitochondrial genome as the proband, were more likely to suffer from a mood disorder than non-matrilineal relatives (Bergemann and Boles, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Since the Y chromosome contains a very limited number of genes and the Barr body (second X chromosome in females) remains largely inactive in healthy cells of the female body [73, 74], the impact of chromosomal differences in the classic sense [19, 299] on anxiety-related behavior is probably small in comparison to developmental or adult neuroendocrine sex differences, but not negligible [35, 89, 241]. The role of the maternally inherited mitochondrial genome and its effects on energy balance should also not be ignored because a higher predisposition for anxiety and depressive disorders is detected in mothers and matrilineal relatives of children with maternally inherited mitochondrial diseases [48], and clinical in vitro fertilization studies among offspring of genetically related or unrelated mothers suggest that, in many cases, affective and anxiety-linked genetic traits may be inherited from the mother [38, 307, 308]. It also to be expected that anxiety-relevant biological sex differences exist with regard to stress vulnerability, meaning how the female brain perceives and processes stressful events, and that some of these differences should be detectable on a molecular level.…”
Section: Major Questions and Challenges For Animal Modelsmentioning
confidence: 99%
“…There is abundant evidence of mitochondrial abnormalities in these patients. For example, one study demonstrated that individuals with early onset MDD are significantly more likely to have a mother with MDD than a father with the disorder, thus supporting the possibility of maternal mitochondrial inheritance in MDD via mutations in mtDNA [207]. However, evidence of variations in mtDNA in clinical populations with MDD is limited.…”
Section: In Vivo Genetic and Post-mortem Studies Of Patients With Pmentioning
confidence: 99%